Editor’s Foreword - Kevin Murry; Socorro Herrera (Educational Considerations, 1999)
This special issue of Educational Considerations focuses on emergent challenges and promising practices in the education of culturally and linguistically diverse [CLD] students in public schools, especially those in ESL classrooms.